2017
DOI: 10.1007/978-3-319-54666-7
|View full text |Cite
|
Sign up to set email alerts
|

FinTech in Germany

Abstract: In this study, conducted on behalf of the Federal Ministry of Finance, we provide the first comprehensive analysis of the German FinTech industry. We quantify the market volume of the industry between 2007 and 2015. On the basis of this data, we also predict the future development of eight segments of the FinTech market, offering detailed forecasts for the years 2020, 2025, and 2035. Moreover, we provide a comprehensive overview of current trends and the drivers of growth that have affected the FinTech industr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
69
0
10

Year Published

2019
2019
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(80 citation statements)
references
References 0 publications
1
69
0
10
Order By: Relevance
“…We identi-fied the startups by using the Nordic Tech List (2018). These startups were "new ventures developing software based financial services" (Dorfleitner et al, 2017) and: i) had received at least 1M (~$1.5M CAD) in funding; ii) had a corporate website in at least two languages; and iii) had been founded in Sweden. According to Lee and Shin's (2018) typology of the business models of fintech startups, the 15 interviewed fintech startups included: capital market (1), insurance (1), crowdfunding (1), wealth management (3) and payment (7).…”
Section: Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…We identi-fied the startups by using the Nordic Tech List (2018). These startups were "new ventures developing software based financial services" (Dorfleitner et al, 2017) and: i) had received at least 1M (~$1.5M CAD) in funding; ii) had a corporate website in at least two languages; and iii) had been founded in Sweden. According to Lee and Shin's (2018) typology of the business models of fintech startups, the 15 interviewed fintech startups included: capital market (1), insurance (1), crowdfunding (1), wealth management (3) and payment (7).…”
Section: Data Collectionmentioning
confidence: 99%
“…Various understandings of the current fintech trends are twinned with ambiguity over just what the term fintech actually covers (Gromek, 2018). A straightforward definition of fintech is "companies... that combine financial services with modern, innovative technologies…, offer [ing] Internet-based and application-oriented products" (Dorfleitner et al, 2017). Offerings of fintech startups relate to a broad range of categories, but particularly to automated wealth management, customized insurance, peer-to-peer lending, new payment solutions, crowdfunding, and the trading of stocks (Lee & Shin, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…"FinTech" is short for two words, financial and technology and literally means financial technology. More broadly, FinTech is a company or part of a company that combines modern financial services with innovative technology (Dorfleitner, Hornuf, Schmitt and Weber 2017). Generally, FinTech attracts consumers through its internet-based products and services, which usually use web applications as the platform, making FinTech more efficient, transparent and automated, and differentiated from conventional financial services.…”
Section: Definition Of Financial Technologymentioning
confidence: 99%
“…Such participants include FinTech companies that are focused on specific activity areas or include several electronic commerce areas and technology companies; however, conventional financial services institutions also seek to apply FinTech innovations and compete with new participants. The literature sources define the following areas of FinTech activities: payment, asset management, loans, pooled financing, insurance services, and capital market (Lee et al, 2017, Schindler, 2016, Dorfleitner et al, 2017, Glomber, 2017.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Although the majority of the research papers on the topic of FinTech is theoretical, rather than empiric in nature (Blach, 2011, Arner et al, 2015, Vaškelaitis, 2010, Dorfleitner et al, 2017, Puschmann, 2016, Schindler, 2016, Walker, 2017, Kalmykova et al, 2015,they provide definitions of financial technologies, define the development stages and operating models, analyze the existing regulations and the impact of technologies, and emergence of risks; however, in view of the further development of the FinTech sector, other areas have also attracted the interest of researchers (Kagan et al, 2005;DeYoung, 2005;Cyree et al, 2009;Trivedi, 2015, Tunay et al, 2015Yen, 2013, Heffernan et al, 2008Buss et al, 2017;Bratasanu, 2017;Mwaura et al, 2016;Levišauskaitė, 2004;Vargas, 2008;Gimpel, 2015;Lee et., 2017;Mansilla-Fernandez, 2017), focusing more on the level of FinTech development of the country, the impact of the sector upon the national economy, the financial sector, or the possibilities of further development of the FinTech sector. For instance, Vargas (2008) found that banks employ financial technologies to a lesser extent than FinTech companies, but their role remains important and banks are likely to increase the use of financial technologies in the future.…”
Section: Literature Reviewmentioning
confidence: 99%